The Role of S100B Protein at 24 Hours of Postnatal Age as Early Indicator of Brain Damage and Prognostic Parameter of Perinatal Asphyxia - Qiu Luo MSc; Tamis Pin PhD; LiFen Dai MD; GuiXian Chen MD; YuTong Chen BSc; FuLu Tian BSc; Man Zhang BSc (SAGE Publishing, 2019)
Introduction. S100B protein is a cytosolic calcium-binding protein with a molecular weight of 21 kDa, which is present in various cells and concentrated mainly in the glial cells, which play a vital role in the maintenance of cellular homeostasis in the central nervous system. It is possible that increased S100B protein level might be considered as sensitive and specific indicator to predict early brain damage. Aim. To investigate the prognostic value of serum S100B protein in neonates with perinatal asphyxia (PA) at 24 hours of postnatal age. Methods. A systematic review was performed. Inclusion criteria were studies including data of neonates with PA, monitored with serum S100B, and with neurodevelopmental follow-up of at least 2 weeks. The period of bibliographic search was until January 2017. The consulted databases were MEDLINE, PsycINFO, and Embase. A combination of the following subject headings and keywords was adapted for each electronic database: "perinatal asphyxia," "hypoxic ischemic encephalopathy," "hypoxia-ischemia, brain," and "S100B." Meta-Disc1.4 software was used. Results. From the 1620 articles initially identified, 6 were finally included and reviewed. The overall diagnostic sensitivity of serum S100B was 0.80 (95% confidence interval [CI] = 0.68-0.88) and the specificity was 0.79 (95% CI = 0.70-0.87). But there was lower predictability value, that is, the positive likelihood ratio was only 3.26 (95% CI 1.74-6.12) and the negative likelihood ratio was 0.32 (95% CI = 0.20-0.5). The diagnostic odds ratio was 12.40 (95% CI = 4.66-33.0). Conclusion. Increased serum S100B level at 24 hours of postnatal life can demonstrate brain damage, but it should not be the only one used to predict PA outcome.